Pemetaan Industri di Kota Batam Menggunakan Mobile GIS Berbasis Android - Zaki A Agha; Andy Triwinarko; Baigo Hamuna (Journal of Applied Informatics and Computing, 2017)
Android-based mobile GIS application is a service that combines digital maps in vector and smartphone media to search industry in Batam. This application is online. Currently, the information presented only provide location of region, users who are not familiar with the location will be difficult or take a long time to find the location of industry. Therefore it is necessary to design an application that is able to provide information on the location of industries in Batam. This thesis did research and development of Android-based mobile GIS applications to provide information on the location of industry in Batam. These applications have been built with the ability to show a map of Batam are taken from GeoServer, handle the search process, displays information and maps location of industry as desired user.